Long-term neurologic outcomes following paediatric out-of-hospital cardiac arrest. (May 2016) - Michiels, Erica; Quan, Linda; Dumas, Florence; Rea, Thomas
Abstract: Aim: Evaluate long-term neurologic outcome for paediatric survivors of OHCA. Methods: Subjects <19 years who experienced OHCA from 1976–2007 and survived to hospital discharge were included. Demographics, neurologic outcomes and years of survival were determined using the King County Emergency Medical Service cardiac arrest database, Seattle Children's Hospital medical records, Washington State Death Database and National Death Index. A Paediatric Cerebral Performance Category (PCPC) score (1–6) was determined for the index hospitalization discharge and all subsequent visits. Results: From 1976–2007, 1683 cases of OHCA resulted in 91 survivors to hospital discharge. 18/91 survivors identified had pre-morbid conditions. 72/91 survivors had follow-up PCPC scores. Patients were: ≤5 years (53%) and 54% female. 33/35 patients with initial favorable neurologic outcomes (PCPC 1–2) maintained favorable neurologic status in long-term follow-up. 14/37 patients with initial unfavorable neurologic outcomes (PCPC 3–5) remained unfavorable over long-term follow-up. Six unfavorable patients showed some improvement, three of whom achieved favorable PCPC scores at last evaluation. One unfavorable patient declined from PCPC 4 to PCPC 5. Twenty patients with an initial unfavorable neurologic outcome died in long-term follow-up. Conclusions: In this cohort study of neurologic outcomes for paediatric OHCA survivors, a favorable initial PCPC score was highly associated with stable long-term neurological outcomes. Those with poor neurologic status at initial discharge were unlikely to improve and were at greatest risk to die in follow-up. Future studies should focus on improving neurologic outcomes and prospectively evaluating the long-term neurologic course.